(η6-Arene) ruthenium(II) complexes with ferrocene-tethered salicylaldimine ligands: Synthesis, characterization and anti-cancer properties. (1st December 2020) - Jakku, RanjithKumar; Eda, Rami Reddy; Mirzadeh, Nedaossadat; Telukutla, Srinivasa Reddy; Vardhaman, Anil Kumar; Lingamallu, Giribabu; Balasubramanian, Sridhar; Deep, Pooja; Sistla, Ramakrisna; Bhargava, Suresh; Trivedi, Rajiv
Graphical abstract: Mixed metal ruthenium-ferrocene complexes with anti-cancer properties. Highlights: Six novel and fully characterised hetero-bimetallic Ru-Fe complexes are reported. The in vitro anticancer activities against two cancer cell lines, HepG2 and HeLa are reported. 5c showed enhanced cytotoxicity against HeLa cancer cells (IC50 = 9.34 compared to 31.32 for cis-pt). 5d showed enhanced cytotoxicity against HepG2 cancer cells (IC50 = 15.74 compared to 27.95 for cis-pt). Abstract: A series of ruthenium(II) complexes (5a -5f ) derived from ferrocenyl salicylaldimine ligands (3a -3f ), coordinated in a chelating mode through the deprotonated phenolic oxygen atom and the imine nitrogen, were synthesized and fully characterised. The molecular structures of selected ligands and complexes were also confirmed by X-ray diffraction analysis. The heterobimetallic Ru-Fe complexes 5a -5f were evaluated for their in vitro anti-cancer activity against human liver cancer (HepG2) and human cervical cancer (HeLa) cell lines and showed better activities compared to the ferrocenyl salicylaldimine ligands. Among the heterobimetallic complexes, 5c and 5d showed enhanced cytotoxicity against HeLa cancer cells (IC50 value of 9.34 µM compared to 31.32 µM for cisplatin), and HepG2 cancer cells (IC50 value of 15.74 µM compared to 27.95 µM for cisplatin), respectively. Mechanistic studies indicated compound 5d induced cell cycle arrest in the S phase. Further, compound 5d treatment resulted in increased ROS generation and loss of mitochondrial membrane potential in HepG2 cells.